Pemanfaatan Media Pembelajaran E-Learning Menggunakan Whatsapp sebagai Solusi di Tengah Penyebaran Covid-19 di SDN Gembong 1 - Ina Magdalena; Andriyanto Andriyanto; Rezi Reki Refaldi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2020)
In the modern era, information technology has experienced very rapid development, especially in education, the use of the internet in education continues to grow. E-leraning is a form of learning that utilizes electronic devices, whether using internet access or not. In the world of education itself, the use of internet access has been widely used for the use of applications / systems as a learning medium. The world of education is currently being shocked by the emergence of the spread of the Covid-19 virus, which indirectly has an impact on the world of education. One of the effects that we feel today is the implementation of online learning for students, from all levels throughout Indonesia. As educators, of course they must be able to adapt appropriately so that the learning process can still run optimally, even though learning is carried out with an online system, of course one of the things that must be prepared by an educator, in order to implement online learning is effectiveness and accuracy in selecting learning media by adjusting the condition of students. One of the media that can be used is Whattshap, because Whattshap has many features such as sending messages, sending pictures, videos, sounds, creating groups and others and is easy to operate. In this paper, we will try to describe how useful WA is in supporting student distance learning, the constraints faced and how the advantages / advantages are.